2022
DOI: 10.1002/ccr3.5699
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive intrasulcular tunneling technique for treatment of gingival recessions: A case series

Abstract: Coronally advanced flap (CAF) by tunneling procedure was applied on four cases of gingival recession. Post‐operative follow‐up, at different time breaks, recorded full coverage of almost all receded root surfaces. The technique and the clinical outcome of this technique will be demonstrated in this case series report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Salem et al reported that the tunneling technique is superior to the traditional CAF procedure in terms of longterm GR coverage [12]. Tunneling techniques have been shown to result in predictable positive outcomes as demonstrated by the results of our study [13]. Our findings are also in accordance with the observations of a previous systematic review [14].…”
Section: Discussionsupporting
confidence: 92%
“…Salem et al reported that the tunneling technique is superior to the traditional CAF procedure in terms of longterm GR coverage [12]. Tunneling techniques have been shown to result in predictable positive outcomes as demonstrated by the results of our study [13]. Our findings are also in accordance with the observations of a previous systematic review [14].…”
Section: Discussionsupporting
confidence: 92%
“…A long free gingival graft of 1 mm thickness was harvested from the palate and completely deepithelialized with a 15c blade ( Figure 2(e) ). The graft was placed under the tunneling pouch and stretched laterally by the sutures, as previously described [ 14 ] and fixed to the facial aspects of the left and right canines with composite, and then, the graft was advanced coronally on the labial surface of the crowns ( Figure 2(f) ). Postoperation medications and instruction were given to the patient.…”
Section: Case Twomentioning
confidence: 99%